Synthesis of Nickel‐Doped Ceria Catalysts for Selective Acetylene Hydrogenation. Issue 5 (14th February 2019) - Riley, Christopher; De La Riva, Andrew; Zhou, Shulan; Wan, Qiang; Peterson, Eric; Artyushkova, Kateryna; Farahani, Majid D.; Friedrich, Holger B.; Burkemper, Laura; Atudorei, Nicu‐Viorel; Lin, Sen; Guo, Hua; et al.
Abstract: Metallic nickel is known to be an active, but not a selective hydrogenation catalyst for conversion of alkynes to alkenes. On the other hand, nickel oxide is not active. Recently, we have demonstrated that nickel doped into ceria provides an inexpensive catalyst for selective hydrogenation of acetylene in the presence of ethylene. Here, we evaluate various synthesis methods to achieve optimal selective hydrogenation performance. We examined incipient wetness impregnation, coprecipitation, solution combustion, and sol‐gel synthesis to study how the method of preparation affects catalytic structure and behavior. Sol‐gel synthesis, coprecipitation, and solution combustion synthesis methods favor nickel incorporation into the ceria lattice, while incipient wetness impregnation creates segregated nickel species on the ceria surface. For hydrogenation of acetylene, these nickel surface species lead to poor ethylene selectivity due to ethane and oligomer formation. However, when nickel is incorporated into the ceria lattice, ethane formation is prevented even while achieving 100 % conversion of acetylene. Coke formation is also significantly reduced on these catalysts compared to conventional nanoparticle counterparts. We conclude that sol‐gel synthesis provides the optimal method for creating a uniform dopant distribution within the high surface area ceria. Abstract : All the single nickel ! Conventional nickel nanoparticle catalysts are unselective for the semi‐hydrogenation of acetylene. Metallic nickel is a deep hydrogenation catalyst, leading to formation of ethane and oligomers from acetylene. Nickel atoms doped into a ceria support provide a selective hydrogenation catalyst. Over‐hydrogenation is prevented, while oligomerization of acetylene is significantly reduced. In this work, methods for synthesizing selective nickel‐ceria catalysts are investigated.